Experimental design impacts the vector competence of Ornithodoros ticks for African swine fever virus: a meta-analysis of published evaluations - Bernard, Jennifer; Vial, Laurence; Madeira, Sara; Otte, Joachim; Boinas, Fernando; Le Potier, Marie-Frédérique; Jourdan-Pineau, Hélène (Peer Community Journal, 2025)

(untitled)
African Swine Fever (ASF) is a highly economically devastating viral disease for swine. Soft ticks of the genus Ornithodoros are involved in its epidemiology, as vectors and natural reservoirs of African Swine Fever Virus (ASFV). The vector competence of Ornithodoros ticks for ASFV has been mainly studied by mimicking natural tick-to-pig transmission pathways through experimental infections in the laboratory. By reviewing the original research studies dating back to the 1960s on the vector competence of Ornithodoros for ASFV, we estimated the vector competence of 10 tick species in association with 38 viral strains resulting in 51 tick-virus associations. This assessment emphasized the extensive range of protocol designs employed and their impact on the success of tick infection with ASFV. Our results call for standardised procedures in vector competence experiments to facilitate further investigation and reduce potential experimental bias. In particular, we recommend the use of late nymphs or adult ticks from a laboratory colony to achieve efficient infection rates. In addition, viral inoculation should be carried out by blood meal rather than by injection, and preference should be given to high titre blood. Finally, detection of viral DNA should be performed 2 months after inoculation to distinguish between successful replication and residual virus in the tick.